Adaptive beamforming of steerable array monopole antenna for WLAN application - Amer Asem, Abdullah (2018)
The modern communication systems are using smart portable devices that operate on WLAN frequency of 2.45 GHz. One of the serious limitations of handled devices is difficult to achieve a direct connection between the transmitter and receiver. Therefore, a smart steerable patter array antenna is highly recommended for new generation communication. Using low-cost steerable passive monopole array antenna can achieve a beam steering and high gain. Loading an additional reactance to the passive elements of the array are changed the mutual coupling between the arrays, which leads to steering the pattern to the desired direction. However, this needs fast process accurate optimised parameters. In this study, four passives one active monopole array antenna is proposed and simulated by using CST Microwave Studio software. The adaptive beamforming is proposed by using downhill simplex algorithm. The results show that the optimum reactance values are suggested after 0.074 second with 94 iterations to achieve a direction of arrival of 180° and 0°. The simulated radiation is successfully steered to the direction of 180 ° by adding the suggested reactance into the passive elements. Furthermore, the antenna gain is improved by 1.3 dBi that achieved a value of 5.3 dBi.The envelope-cross-correlation (ECC) shows magnitudes less than 0.5 among the elements. This algorithm successfully is provided with the optimum reactance values. The proposed approach can be considered a fast and significant candidate for new generation of smart communication WLAN applications.